Percepción de médicos especialistas sobre la usabilidad de una aplicación móvil de dengue en zonas rurales: un estudio cualitativo - De la Cruz-Torralva, Kelly (2024)
Introduction. Mobile applications represent a promising alternative for providing support in the management of Dengue patients. However, the usability of these tools in Peru is unknown. Objectives. To evaluate the usability and usage recommendations of the Dengue ONQOY application in managing Dengue patients in rural areas of Peru. Methods. A qualitative study was conducted, which included semi-structured interviews with 8 experts in Dengue management. Data were coded using Atlas. Ti software. Three categories were assessed: (1) informative usability (2) design usability, and (3) recommendations for improvement. Results. Three key aspects were highlighted. (1) The application is perceived as valuable for first- level doctors in peripheral areas with limited Dengue experience due to its personalized approachand academic value. (2) Its ease of use and practicality were emphasized, although connectivity limitations in some areas were noted. (3) Recommendations for improvement included the inclusion of differential diagnoses, additional risk factors, updated references, hydration guidelines, and medication dosages. Conclusions. Dengue ONQOY is considered highly usable by doctors treating Dengue cases at the primary care level in Peru. Despite connectivity limitations and potential design improvements, its development and implementation offer a promising alternative for managing Dengue patients in the country in this field.